The Relationship Between Maternal Knowledge of Posyandu and Toddler Attendance at Posyandu in Melungun Ratu Village, North Lampung Regency, 2025 - Riona Sanjaya; Adinda Halimatusakdiah; Hellen Febriyanti; Rika Agustina (Jurnal EduHealth, 2026)
Integrated Health Service Posts (Posyandu) represent a strategic effort to improve maternal and child health status through promotive and preventive activities at the community level. However, low attendance rates among toddlers at Posyandu remain a significant issue. According to the 2024 Batu Nangkop Health Center report, of the 1,101 target toddlers in Melungun Ratu Village, only 548 (49.7%) participated in weight monitoring a figure far below the established target of 85%. This condition reflects low maternal participation in Posyandu activities, which potentially hinders early detection of nutritional disorders and childhood developmental delays. This study aims to analyze the relationship between mothers' knowledge levels regarding Posyandu and the frequency of toddler visits. A quantitative research design with a cross-sectional approach was employed. The study was conducted in July 2025 at the Melungun Ratu Village Posyandu with a sample of 65 respondents selected via total sampling. The research instrument consisted of a questionnaire, and data analysis was performed using the chi-square test. The results indicated that the majority of toddlers visited Posyandu irregularly (60%), and most mothers possessed a low level of knowledge (52.3%). Chi-square analysis yielded a p-value of 0.000 (p < 0.05), indicating a significant relationship between maternal knowledge and toddler attendance at Posyandu. The Odds Ratio (OR) of 29.7 indicates that mothers with good knowledge are 29 times more likely to bring their toddlers to Posyandu regularly compared to those with poor knowledge. It is recommended that healthcare workers and Posyandu volunteers enhance counseling and health education efforts to foster maternal awareness regarding the importance of Posyandu in monitoring toddler growth and development.